Program to Promote Personal and Social Responsibility in the Secondary Classroom - Carbonero, Miguel A.; Martín-Antón, Luis J.; Otero, Lourdes; Monsalvo, Eugenio (Frontiers in Psychology, 2017)
The performance of school children has been studied by considering partial relationships between several personal variables such as the link between cognition and motivation. However, contextual variables, such as a child’s willingness to accept social responsibility, also influence students’ social and academic performance. Thus, students with greater responsibility have a better attitude towards their studies, resulting in higher academic achievement. This two-year study aims to reveal to what extent an intervention program affects student performance and is based on the Theory of Positive Action among young people proposed by Don Hellison and the Theory of Reasoned Action by Fishbein and Ajzen. The program focuses on positive influences on social and personal responsibility, taking into consideration parental styles, gender and academic performance. The program was a part of the educational curricula in participating schools and it targeted four main areas: (a) teaching units using academic texts about social responsibility, (b) student training in mediation processes, (c) teacher training, and (d) family training and involvement. A total of 271 students took part from first and second year of Secondary Education (12-14 years old). The experimental group was made up of 132 students while the remaining 139 formed the control group. All participants completed the Assessment Scale of Social Responsibility Attitudes in Secondary Education and the Parent-Adolescent Communication Scale. Results show that students in the experimental group performed significantly better than those in the control group. Additionally, the issue of Social Responsibility seems to be related to commitment, self-discipline and perseverance. Regarding gender, males appear to score higher in the factor for well-mannered, friendly and tidy. Finally, a positive relationship has been identified between social responsibility attitudes and parenting with an open communicational style. This paper discusses the results so that schools can include programs aimed at improving social and personal responsibility.